An Automated Method for the Determination of Intestinal Disaccharidase and Glucoamylase Activities. (2006) - He, Zhaoping; Bolling, Laura; Tonb, Dalal; Nadal, Tracey; Mehta, Devendra I.
Abstract : Determination of disaccharidase and glucoamylase activities is important for the diagnosis of intestinal diseases. We adapted a widely accepted manual method to an automated system that uses the same reagents reaction volumes, incubation times, and biopsy size as the manual method. A dye was added to the homogenates as the internal quality control to monitor the pipetting precision of the automated system. When the automated system was tested using human intestinal homogenates, the activities of all the routinely tested disaccharidases, including lactase, maltase, sucrase, and palatinase, as well as the activity of glucoamylase, showed perfect agreement with the manual method and were highly reproducible. The automated analyzer can perform the same routine assays of disaccharidases and glucoamylase with high consistency and accuracy and reduce testing costs by performing a larger sample size with the same number of staff. Additional developments, such as barcoding and built-in plate reading, would result in a completely automated system.